Designing the human stress ontology: A formal framework to capture and represent knowledge about human stress - Khoozani, Ehsan; Hadzic, Maja (Taylor and Francis Ltd, 2010)
A large number of papers have been published on the topic of human stress. There is a need to organise this knowledge under a unifying framework, linking and analysing it in mutual combinations so that new knowledge can emerge. Ontology is an enriched conceptual model for representing domain knowledge. An ontology can be designed to provide a framework for knowledge about human stress. This agreed knowledge model will facilitate knowledge sharing and communications. Additionally, ontologies are machine-readable and can enable automated programs such as data mining to intelligently access and analyse information. The purpose of this paper is to discuss and explain some of the common stress-related terms, their definitions, classifications and possible interrelations between them. A top-layer of the human stress ontology (HSO) model is presented, which will continue to evolve as more research contributions and knowledge become available. It is believed that this framework can be used to build powerful tools to assist researchers and therapists in evaluating stress and facilitating their communication in both research and clinical spaces.